The Making of Western Jewry, 1600-1819 - Kochan, L. author. aut Link
X, 390 p.
Keywords: In a broad sweep from Central Europe to Ireland and from the Sixteenth to the early Nineteenth-century, this work puts the Jewish community and its rabbinic and 'lay' leaders at the centre of Jewish history. Of surpassing value is Kochan's treatment of the community not only as a religious but also as a political unit.